Protocol to assess changes in brain network resistance to perturbation during offline processing using TMS-EEG - Martina Bracco; Tuomas P. Mutanen; Domenica Veniero; Gregor Thut; Edwin M. Robertson (STAR Protocols)
Summary: Transcranial magnetic stimulation (TMS) perturbs specific brain regions and, combined with electroencephalography (EEG), enables the assessment of activity within their connected networks. We present a resting-state TMS-EEG protocol, combined with a controlled experimental design, to assess changes in brain network activity during offline processing, following a behavioral task. We describe steps for experimental design planning, setup preparation, data collection, and analysis. This approach minimizes biases inherent to TMS-EEG, ensuring an accurate assessment of changes within the network.For complete details of the use and execution of this protocol, please refer to Bracco et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.